Integrasi learning management system (lms) dalam pembelajaran digital: tinjauan pedagogis, teknologis, dan kelembagaan - RAHMADANI, MUHAMMAD RIAN NUR (Maliki Interdisciplinary Journal, 2026)
The rapid development of digital technology has driven fundamental transformations in higher education, particularly in utilizing Learning Management Systems (LMS) as platforms to support learning activities. LMS should be viewed not merely as a content delivery medium, but as an integrated system that manages learning processes, assessments, and academic interactions in a structured and comprehensive manner. This article aims to analyze the use of LMS in digital learning through an interdisciplinary perspective, encompassing pedagogy, educational technology, and institutional policy dimensions. This study employs a literature review method by analyzing various relevant research discussing LMS implementation within higher education institutions. The findings indicate that LMS enhances learning flexibility, significantly promoting student autonomy, and supporting the effective implementation of blended learning models. However, LMS utilization faces several serious challenges, including users’ digital literacy readiness, infrastructure limitations, and the need for stronger institutional policy support. Therefore, optimizing LMS requires continuous synergy among technological development, pedagogical innovation, and institutional commitment to ensure the sustainability and quality of digital learning in the future.